2013
DOI: 10.1186/1756-3305-6-63
|View full text |Cite
|
Sign up to set email alerts
|

Compound DNA vaccine encoding SAG1/ SAG3 with A2/B subunit of cholera toxin as a genetic adjuvant protects BALB/c mice against Toxoplasma gondii

Abstract: BackgroundIntracellular parasites, such as T. gondii, present a plurality of antigens because of the complexity of its life cycle. Compound DNA vaccines bring a new approach and hope for the treatment of toxoplasmosis. In this study, a DNA vaccine encoding two major surface antigens SAG1, SAG3 from T. gondii, with A2/B subunit of cholera toxin as a genetic adjuvant was constructed.MethodsBALB/c mice were immunized intramuscularly with PBS, pcDNA3.1, pSAG1, pSAG1/SAG3 and pSAG1/SAG3-CTXA2/B three times separate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 32 publications
0
16
0
2
Order By: Relevance
“…This is in agreement with Zaharoff et al (2007) who used b-galactosidase vaccine in either chitosan solution or FIA and reported no significant difference between them. A significant increase in IFN c level was also obtained by Meng et al (2012), Chuang et al (2013), Zhao et al (2013a) and Cong et al (2013).…”
Section: Discussionmentioning
confidence: 74%
“…This is in agreement with Zaharoff et al (2007) who used b-galactosidase vaccine in either chitosan solution or FIA and reported no significant difference between them. A significant increase in IFN c level was also obtained by Meng et al (2012), Chuang et al (2013), Zhao et al (2013a) and Cong et al (2013).…”
Section: Discussionmentioning
confidence: 74%
“…The levels of cytokines were detected by a previously described method (Cong et al, 2013). Four weeks after the last booster vaccination, spleens were isolated from euthanized mice (three mice per group).…”
Section: Spleen Cell Cultures and Cytokine Quantificationmentioning
confidence: 99%
“…The proteins produced from DNA vaccine in vivo are presented as both MHC class I and II molecules [4]. In this direction, the plasmid pcDNA3.1(+) was used as a vector for DNA vaccine construction [23,24] and proved efficient for the expression of CsAg17 protein in FVB mice.…”
Section: Discussionmentioning
confidence: 99%